Interference analysis between IMT-2020 (5G) system and broadcasting satellite service system in the band of 24.65～25.25 GHz - Rui HAN; Lei ZHANG; Wei LI; Shanshan LIU; Guan WANG; Chunhua LIU (Dianxin kexue)
Based on the Agenda Item 1.13 of WRC-19 and requirements for domestic compatibility analysis of 5G candidate frequency bands above 6 GHz,the interference from IMT-2020 system (5G) to broadcasting satellite service system in 24.65～25.25 GHz band was studied.The Monte Carlo simulation method was used to assess the aggregate interference from IMT base station (BS) to the up-link of feeder link of broadcasting satellite where the geostationary orbit satellite at 59℃,85℃ and 113℃ longitude.The aggregate interference level from 5G system to the two kinds of carriers of the satellite system with different orbits was evaluated via simulation analysis.Research results show that the IMT-2020 (5G) system will not cause harmful interference for broadcasting satellite services system.The results can provide technology basis for future planning of IMT-2020 (5G) system in millimeter wave and protecting of broadcasting satellite system.